Principal Strategies for Improving Students’ Literacy Skills - Mardalena Mardalena; Nila Kesumawati; Nuril Furkan (Journal of Social Work and Science Education, 2027)
This article analyzes principal strategies for improving students’ literacy skills in an integrated Islamic junior high school context. The study was developed from qualitative case study conducted at SMP IT Al-Furqon Palembang. The research focused on four main aspects: the planning and implementation of the principal’s literacy strategy, the challenges and solutions in program implementation, the principal’s leadership role in strengthening literacy culture, and the impact of the strategy on students’ literacy development. Data were collected through in-depth interviews, participatory observation, and documentation involving the principal, school supervisor, curriculum vice principal, teachers, students, and parents. The findings show that the principal acted as both an instructional and transformational leader by integrating literacy into school vision, curriculum, classroom learning, Islamic values, and school culture. The main strategy was organized through Penggiat Literasi Al-Furqon (PELITA), including literacy corners, digital literacy, bulletin publication, wall magazines, book writing, and appreciation for active library users. Although the implementation faced challenges related to teacher competence, student reading interest, data-based evaluation, learning time, reading resources, and gadget influence, the school responded through teacher training, peer tutoring, varied literacy methods, strengthened coordination, and parent involvement. The strategy improved students’ literacy achievement, participation, confidence, creativity, and learning culture.